Metabolome and microbiome analysis revealed the effect mechanism of different feeding modes on the meat quality of Black Tibetan sheep - Zhang, Xue; Han, Lijuan; Gui, Linsheng; Raza, Sayed Haidar Abbas; Hou, Shengzhen; Yang, Baochun; Wang, Zhiyou; Ma, Ying; Makhlof, Raafat T. M.; Alhuwaymil, Zamzam; Ibrahim, Samah F. (Frontiers in Microbiology, 2023)
This study applies metabolomics-based analyses of muscles and 16S rDNA-based sequencing of rumen fluid to examine how feeding regimes influence the composition of rumen microbiota, muscle metabolism and ultimately the quality of meat from Black Tibetan sheep. The results showed that, compared with BG (indoor feeding with pasture grazing group) and CG (pasture grazing group), SG (indoor feeding group) improved the quality of carcass from Black Tibetan sheep by preventing a decline in pH and increasing fat deposition to enhance the color, tenderness and water holding capacity (WHC) of the longissimus lumborum (LL). Metabolomics and correlation analyses further indicated that the feeding regimes primarily altered amino acid, lipid and carbohydrate metabolism in muscles, thereby influencing the amino acid (AA) and fatty acid (FA) levels as well as the color, tenderness and WHC of the LL. Furthermore, SG increased the abundance of Christensenellaceae R-7 group, [Eubacterium] coprostanoligenes group, Methanobrevibacter, Ruminococcus 2 and Quinella, while decreasing the abundance of Lactobacillus, Prevotella 1, Succinivibrio, Rikenellaceae RC9 gut group and Selenomonas 1. Interestingly, all of these microorganisms participated in the deposition of AAs and FAs and modified the levels of different metabolites involved in the regulation of meat quality (maltotriose, pyruvate, L-ascorbic acid, chenodeoxycholate, D-glucose 6-phosphate, and glutathione etc.). Overall, the results suggest that feeding Black Tibetan sheep indoors was beneficial to improve the mouthfeel of meat, its color and its nutritional value by altering the abundance of rumen bacteria which influenced muscle metabolism.